Modeling accessibility of community facilities using GIS: case study of Depok City, Indonesia - Herika Muhamad Taki; Muhammad Zainuddin Lubis (Politeknik Negeri Batam, 2017)
Improving community accessibility based on transport connectivity helps to address equity issues. Geographical information systems (GIS) provide useful techniques for capturing, maintaining and analyzing spatial data to defining community issues. The objective of this study is to model accessibility of community facilities using GIS based on private car, bus and train in the city area of Depok, Indonesia. The study modeling the accessibility of community facilities using Geographical information systems (GIS). A geodatabase of community facilities that includes the location of the mall, schools, hospital, mosque, and lake and also supporting data such as street and road network, the number of population, density and land use. The geodatabase covers defining community facilities and modeling accessibility by car, by bus, and by train and analyzing the social pattern. The results obtained from the spatial pattern of accessibility based on the different modes of transportation using the method of network analysis and buffering operations underlines the existence of different patterns. Car transport mode is a commonly accessible mode of community-related to land use interpretation and social issues. The conclusion is that there are differences in the spatial models at the city level in terms of the use of transportation accessibility